(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The occurrence of Aleurolobus niloticus Pr. & Hos. in Italy is pointed out in the present note. A morphological description of the insect is provided, together with little information on its geographical distribution, host plants, biology and economic importance in relation to the attacked plants. Moreover, the malli. differences between the insect and its congeneric species known in our country are traced and a key for the identification of the ltalian species of the genus Aleurolobus Quaint. & Baker is provided.